1998
DOI: 10.1046/j.1365-2559.1998.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of follicular dendritic cells in nodular sclerosing Hodgkin's disease

Abstract: Aims In nodular sclerosing Hodgkin's disease (NSHD), the prognostic relevance of the histopathological grading in two subtypes NSI (low‐grade) and NSII (high‐grade) remains controversial. Analysis of follicular dendritic cells (FDC) may provide new prognostic parameters. Methods and results Tumours from 59 patients with NSHD were studied. Mean follow‐up time was 8 years. Forty‐one cases were classified as NSI and 18 as NSII. FDC were immunostained with the paraffin‐resistant monoclonal antibodies CD21 and CNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
9

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
1
6
0
9
Order By: Relevance
“…Earlier studies have examined the association of FDCs with the clinical outcome in patients with CHL, and an intermediate prognosis was reported in FDC-positive cases by immunohistochemistry (44% of the cases studied) compared to a guarded prognosis for the FDC-negative cases [67]. Similar results were reported in another study, although it was mainly confined to the nodular sclerosis subtype of CHL, where the authors reported the presence of FDC meshworks, whether intact or disrupted, in about 70% of their cases and that the cases with intact FDC meshworks exhibited relatively better prognosis than those with disrupted meshworks and a much better prognosis than those with absent FDC staining by immunohistochemistry [66].…”
Section: Fdcs In Classical Hodgkin Lymphomasupporting
confidence: 82%
See 3 more Smart Citations
“…Earlier studies have examined the association of FDCs with the clinical outcome in patients with CHL, and an intermediate prognosis was reported in FDC-positive cases by immunohistochemistry (44% of the cases studied) compared to a guarded prognosis for the FDC-negative cases [67]. Similar results were reported in another study, although it was mainly confined to the nodular sclerosis subtype of CHL, where the authors reported the presence of FDC meshworks, whether intact or disrupted, in about 70% of their cases and that the cases with intact FDC meshworks exhibited relatively better prognosis than those with disrupted meshworks and a much better prognosis than those with absent FDC staining by immunohistochemistry [66].…”
Section: Fdcs In Classical Hodgkin Lymphomasupporting
confidence: 82%
“…phenotype of CHL (positive for CD15 and CD30, faintly positive for Pax-5, and negative for CD45 and CD20). In the authors' experience as well as in few reported studies, the FDC meshworks are usually present and are relatively intact in the nodules and sometimes may be distributed in a pattern similar to that seen in NLPHL [65,66].…”
Section: Fdcs In Classical Hodgkin Lymphomamentioning
confidence: 58%
See 2 more Smart Citations
“…The abnormal cytokine pattern in HL may contribute not only to the proliferation of H/RS cells but also to the maintenance of an inappropriate environment in which an effective host immune response to H/RS cells cannot be achieved. The role of the reactive microenvironment was found to be associated with the number, subset type, and activation state of the reactive immune cells (15,16), specifically the cytotoxic and regulatory T cells (17 -19). However, the full significance of infiltrating immune cells in the pathology of HL continues to be controversial (20).…”
mentioning
confidence: 99%